The Effect of Vegetation in Various Canyon Geometry on The Thermal Comfort of Jakart - Bayu Krisna Suryantara; Jatmika Adi Suryabrata; Alexander Rani Suryandono (Departement of Architecture, Universitas Islam Indonesia, 2019)
Buildings as absorber and heat reflectors can increase air temperature and as shaper formers can lower air temperature. However, both of these roles affect the extent of urban thermal environment, need to be studied through the form of canyon geometry creation of thermal comfort conditions outside space. The focus of this study is to examine how much the relationship between the vegetation and canyon geometry of urban thermal comfort in the humid tropics especially in Jakarta. This research used computer simulation method with hypothetic building object, to test how big influence of vegetation regulation on various canyon geometry to outdoor thermal comfort. Elements of canyon geometry that apply is aspect ratio and orientation. Because these two elements are the most influential elements in thermal comfort. The vegetation applied for this research is grass, greenroof extensive, intensive greenroof, greenwall and trees. Application of the vegetation in increasing thermal comfort is more effective than changing canyon geometry. However, the application of the vegetation will be more effective when applied in accordance with the canyon geometry.Keywords: canyon geometry, vegetation, outdoor termal comfort